Application of Internet-based multidisciplinary management in patients with genitourinary cancers in China: A brief introduction to a new model of healthcare service for cancer survivors during COVID-19 pandemic - Yu Zhu; Yu Zhu; Yu Zhu; Yu Zhu; Shengming Jin; Shengming Jin; Shengming Jin; Shengming Jin; Hangcheng Fu; Hangcheng Fu; Hangcheng Fu; Hangcheng Fu; et al. (Frontiers Media S.A., 2022)
The coronavirus disease 2019 (COVID-19) pandemic has triggered multiple global healthcare system crises. Apart from the pandemic itself, the travel restriction and social distance policy for the purpose of epidemic control has cast a shadow on the management of cancer survivors. Cancer survivors suffered a double blow from both the epidemic and cancer. To deal with the challenge, we explored a new Internet-based patient management model. This model has overcome the limitation of time and space and thus can help oncologists to provide remote multidisciplinary healthcare services for cancer survivors. These patients can get high-quality cancer management from multidisciplinary experts without too much transportation. This model has been applied in patients with genitourinary cancers and proved to be effective and efficient. Our study demonstrated that more patients benefited from this model during the pandemic of COVID-19, especially in those affected heavily by COVID-19. These results suggested that it can also give insight into the management of other cancer survivors in China. Given the long-term impact of the COVID-19 pandemic, we would like to introduce our new model of healthcare service and the application of Internet-based multidisciplinary management to our global peers and medical industries to help their cancer survivors who are delayed in treatment due to the COVID-19 pandemic.